2015
DOI: 10.1039/c5ob00454c
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free cascade cyclization of alkenes toward perfluorinated oxindoles

Abstract: A simple AIBN-mediated cyclization reaction of activated alkenes toward perfluorinated oxindoles is developed. In the presence of readily available AIBN, N-arylacrylamide and perfluoroalkyl iodides underwent perfluorination reaction to give perfluorinated oxindoles in good to excellent yields under metal-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The synthetic application of TfNHNHBoc ( 2a ) as a trifluoromethylating agent was further demonstrated in the tandem trifluoro­methylation/cyclization of N -arylacrylamides for the construction of functionalized oxindoles, which has been found in many biologically relevant compounds . The tandem trifluoromethylation/cyclization of N -arylacrylamides was initially reported to be catalyzed by transition metals, and later several metal-free versions were disclosed using Togni’s reagent, TMSCF 3 , Langlois’ reagent, and CF 3 I as CF 3 sources . While the metal-free versions are more environmentally benign, they required a large excess of CF 3 sources and a long reaction time.…”
mentioning
confidence: 99%
“…The synthetic application of TfNHNHBoc ( 2a ) as a trifluoromethylating agent was further demonstrated in the tandem trifluoro­methylation/cyclization of N -arylacrylamides for the construction of functionalized oxindoles, which has been found in many biologically relevant compounds . The tandem trifluoromethylation/cyclization of N -arylacrylamides was initially reported to be catalyzed by transition metals, and later several metal-free versions were disclosed using Togni’s reagent, TMSCF 3 , Langlois’ reagent, and CF 3 I as CF 3 sources . While the metal-free versions are more environmentally benign, they required a large excess of CF 3 sources and a long reaction time.…”
mentioning
confidence: 99%
“…On the basis of the above experimental results and previously reported mechanisms, a possible mechanism was proposed, as outlined in Scheme . First, the photocatalyst [ fac -Ir­(III)­(ppy) 3 ] is irradiated to the excited state [ fac -Ir­(III)­(ppy) 3 *] under visible light irradiation, which is oxidatively quenched by CF 3 (CF 2 ) 2 CF 2 -I to generate a [ fac -Ir­(IV)­(ppy) 3 ] + complex, a n -C 4 F 9 • radical ( A • ), and an iodine anion.…”
Section: Resultsmentioning
confidence: 72%
“…In the past few years, visible-light photoredox catalysis has been developed as an eco-friendly and highly efficient strategy with the advantages of convenience, availability, and safety. In light of the excellent reductive ability of a photocatalyst in the excited state under mild conditions, photosensitized methods for the generation of perfluorinated radicals from inexpensive and diverse perfluoroalkyl halides are feasible and efficient means for ATRA-type reactions . In general, perfluoroalkyl iodides or bromides were commercially available and much less expensive than other frequently encountered perfluoroalkylating reagents (e.g., Togni’s reagents and R f SO 2 Cl) on a large scale. With our long-standing interest in the difunctionalization of alkenes using perfluoroalkyl halides, we herein demonstrated a visible-light-induced ATRA and cyclization of benzene-tethered 1,7-enynes or N -tethered 1,6-enynes with perfluoroalkyl halides, which realize the concomitant formation of the C-R f and C-X (X = I, Br) bond under mild conditions, leading to 2,4-dihydronquinolin-2­(1 H )-ones and pyrrolidines bearing a wide variety of perfluorinated groups, such as CF 3 , CF 2 Br, C 3 F 7 , C 4 F 9 , C 6 F 13 , C 8 F 17 , C 10 F 21 , CF 2 CO 2 Et, etc (eq 4, Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in 2015, Tang and co-workers reported an AIBN-mediated cyclization reaction toward perfluorinated oxindoles under metal-free conditions (Scheme 29). 55 In this protocol, the authors, for the first time, used readily available AIBN as initiator and low-cost R F I as fluorine source to achieve a highly practical means to produce a broad range of perfluorinated oxindoles. In the presence of AIBN instead of CuBr, the yield of desired products was clearly improved; the results showed that oxidant was beneficial for reaction, and it was demonstrated that DTBP was the optimal oxidant.…”
Section: Account Synlettmentioning
confidence: 99%